Microbiological and cytopathological evaluation of pap-smears among intrauterine device users - Discacciati, Michelle G.; Simões, José Antônio; Montemor, Eliana B.L.; Portugal, Priscila M.; Balys, Adriana L.C.; Montiz, Douglas M. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: intrauterine device (IUD) users could present higher frequency of vaginal tract infections and related complications, such as pelvicin flammatory disease (PID). Objective: to compare the frequency of microbiological and cytopathological alterations in Papsmears among IUDusers and not users. Methods: this is a case-control study of cervical smear from 104 IUD users compared with Pap smears from 104 women notusers of IUD. These smears were stained by Papanicolaou technique and analyzed according to microbiological and citopathological standard criteria. Among the IUD users were also collected samples from vaginal fornix and stained by GRAM and Papanicolaou technique. Statistical analyseswere expressed as odds ratio, with confidence interval of 95%. Results: significant difference was not found in citopathological alterations fre-quency, such as Candida spor Trichomonas vaginalis detection between the groups. Bacterial Vaginosis was higher among IUD (23%) in compari-son to not users (14%). However this difference was not statistically significant. The most impressive result was the detection of Actnomycesspponly in IUD women users (7%) and in samples collected from the uterine cervix. Conclusion: there were no significant differences in detection of citopathological alterations, BV, Candidasp or Trichomonassp between the two groups. IUD women users have higher frequency of Actinomycesspp in comparison to not users. In addition, Papanicolaou smear collected from cervix can be success fully used to diagnose this infection.